Meningkatkan Ketahanan Duduk Anak Hiperaktif Melalui Media Mozaik Di Kelas II SLB Hikmah Miftahul Jannnah Padang (Single Subject Research Di Slb Hikmah miftahul Jannah Padang) - Fidyah Citra Dirna (Universitas Negeri Padang, 2014)
Abstrack: Research carried out on a boy, hyperactive behavior. Observations were made with three sessions: the first session of the baseline (A1) performed eight times, resilience seat in this condition lies in the range of 1-2 minutes, the session intervention (B) by using the media mosaic done ten times, endurance time sitting on the hyperactive child this condition lies in the range of 1-4 minutes and baseline (A2) performed eight times in the range of 1-3 minutes. The percentage of overlap in the baseline condition (A1) 0% and the percentage of overlap in the baseline condition (A2) 33%. Thus the hypothesis is accepted, meaning the length of time endurance hyperactive child sitting in class II SLB Miftahul Jannah Padang Lessons can be increased. Kata kunci: media mozaik, hiperaktif, ketahanan duduk